2020
DOI: 10.1097/ncc.0000000000000794
|View full text |Cite
|
Sign up to set email alerts
|

Development and Psychometric Evaluation of a New Short Version of the Swedish Frommelt Attitudes Toward Care of the Dying Scale

Abstract: Background The Frommelt Attitudes Toward Care of the Dying (FATCOD) is widely used as a measure of attitudes toward care of dying patients. However, poor factor structure and item redundancy have been reported across the literature. Objective A short version of the questionnaire is needed, to facilitate effective assessments of the attitudes of those caring for dying patients. The purpose of this study was to develop a FATCOD–Short Form and to secure it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 35 publications
(120 reference statements)
0
15
0
Order By: Relevance
“…This study examined two revisions of the original 30-item FATCOD in which the scale was reduced to a subset of functioning items [16,17]. Seven items (8,9,11,13,14,26,28) were selected in both studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study examined two revisions of the original 30-item FATCOD in which the scale was reduced to a subset of functioning items [16,17]. Seven items (8,9,11,13,14,26,28) were selected in both studies.…”
Section: Resultsmentioning
confidence: 99%
“…Seven items (8,9,11,13,14,26,28) were selected in both studies. Five items (3,5,6,7,15) were only retained in the previous study of the authors [16] and 2 items (25,29) were isolated in the study of Browall and colleagues [17]. Considering the results of these two independent revisions, a joint set of 14 items was tested using IRT models (partial credit model (PCM) and rating scale model (RSM) specifications).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other short-version studies validated in samples of palliative care professionals and with good psychometric results are discussed in the scientific literature, for example, the Bugen Scale Of Coping With Death [ 40 ] or the Swedish Frommelt Attitudes Toward Care of the Dying Scale [ 44 ]. It is worth highlighting the importance of the availability of brief surveys for use in demanding work contexts such as end-of-life care in order to help protect these staff and not overload them with long questionnaires that further increase their burden and stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research has shown some controversy regarding differences in professionals’ quality of life in relation to these variables [ 24 , 46 59 ], and so future research should examine this possible explanation. Several studies have noted that sex is an important variable because women experience more BO than men [ 43 , 44 ]. However, very few studies have examined sex differences related to CF.…”
Section: Discussionmentioning
confidence: 99%